Role of (Local) Culture in English Language Teaching - Shrestha, Kumar Narayan (Journal of NELTA, 2016)
Since language and culture have muscle and bone relationship, the existence of one in the absence of another in unthinkable. But in practice, English language teaching has paid less attention to the local culture. It is commonly believed that the insertion of foreign cultural values is not in line with local cultural values. The insertion of local culture plays vital role in promotion of nationalism, different local cultures and local cultural wisdom. Similarly, it provides cultural identity and meaningful context for learning. Therefore, the main purpose of this article is to shed light on the importance of local culture in the English language classroom. In doing so, it aims at defining culture, language, shows relationship between them and puts forth some pedagogical guidelines. Journal of NELTA, Vol. 21, No. 1-2, 2016, Page:54-60